SAT0504 How Experts on Autoinflammatory Diseases Classify Inherited Periodic Fevers and Pfapa: Preliminary Results of the Eurofever Delphi Survey. (9th June 2015) - Federici, S.; Vanoni, F.; Ozen, S.; Frenkel, J.; Lachmann, H.; Martini, A.; Ruperto, N.; Hofer, M.; Gattorno, M.
Abstract : Background: Provisional evidence-based classification criteria for inherited periodic fever (TRAPS, FMF, MKD and CAPS) have been recently developed based on the Eurofever registry. However, no consensus on how to combine clinical criteria with results of molecular analysis has been reached so far. Moreover evidence-based classification criteria on PFAPA are still lacking. Objectives: To understand how physicians involved in the clinical care of patients with Autoinflammatory diseases (AIDs) classify patients with inherited periodic fever and PFAPA in daily practice. Methods: By using the Delphi and Nominal Group Technique, we started an initial phase of three following e-mail surveys. In the first survey, clinicians/biologists or other health professionals working in the field of autoinflammation were asked to identify the variables that they consider as important, in the current clinical practice, for the diagnosis of patients with inherited periodic fever and PFAPA. This survey was open to not influence the experts. Results: We sent the first survey to 129 experts. The overall rate of response was 102 (79%): 96 experts responded to be interested in the survey and 72 completed and confirmed it; 6 experts responded not to be interested. Up to date, we have analysed 44 experts' survey. Not all the participants completed the survey for each disease. The table shows the preliminary results of the analysis. There was any clinical variable chosen by all the participants for the five diseases. For a high rate of experts, a positive genetic test is a relevant element for the diagnosis of FMF, TRAPS and MKD. Conversely, for the PFAPA the exclusion of the inherited genetic periodic fever by genetic test is important for a little part of experts. The response to treatment was proposed as interesting variable for FMF, CAPS and PFAPA. Conclusions: The preliminary results of the first Eurofever Delphi Survey show a high rate of response, underlying the interest of the scientific community in this topic. There is a wide heterogeneity in the experts' response for each disease. At the end of the Delphi Survey rounds, we will obtain different set of clinical criteria and we will verify their performance in comparison to already existing criteria in a cohort of patients with inherited periodic fever and PFAPA enrolled in the Eurofever Registry. The final step will be a Consensus among experts (geneticists and clinicians) in order to define the best combination of clinical and genetic data for the definitive classification of patients with inherited periodic fevers and PFAPA. Disclosure of Interest: None declared